Acupuncture for the treatment of obesity in adults: a systematic review and meta-analysis. Issue 1106 (8th July 2017) - Zhang, Rong-Qiang; Tan, Jiao; Li, Feng-Ying; Ma, Yong-Hong; Han, Li-Xin; Yang, Xiao-Li
ABSTRACT: Objective: Meta-analysis was used to assess the clinical efficacy of acupuncture treatment for simple obesity and to provide evidence-based medical data for treating obesity with acupuncture. Methods: A comprehensive search of studies on MEDLINE, EMBASE, the Cochrane Central Register of Controlled Trials and Chinese databases (Wan Fang, CNKI and VIP) from 1 January 1915 through 30 November 2015 (MEDLINE search updated through 31 December 2015) was performed. We included only randomised controlled trials (RCTs) that used acupuncture and sham acupuncture to treat simple obesity. The effect of acupuncture on simple obesity was measured using body mass index (BMI), body fat mass (BFM), waist circumference (WC), hip circumference (HC), and body weight (BW). The Jadad scale was used to assess methodological quality. The random effects model was used in the pooled analysis to adjust for the heterogeneity of the included studies, and funnel plots were used to examine publication bias. The differences between treatment groups were reported as mean differences (MD). Results: Eleven RCTs were selected after all relevant literature from the electronic databases had been screened. There were 338 and 305 participants in the acupuncture and sham acupuncture groups, respectively. Auricular and electro acupuncture were both able to reduce BMI in obese patients (MD 0.47 kg/m 2, 95% CI 0.35 to 0.58, p<0.001; MD 0.50 kg/m 2, 95% CI 0.38 to 0.62, p<0.001). BFM change after acupuncture treatment compared with sham treatment was statistically significant (MD 0.66 kg, 95% CI 0.51 to 0.80, p<0.001). There were also significant differences in WC and HC between the acupuncture and sham acupuncture groups (MDwc 2.02 cm, 95% CI 0.21 to 3.83, p=0.03; MDHC 2.74 cm, 95% CI 1.21 to 4.27, p=0.0004). BW was not statistically significantly different between the acupuncture and sham acupuncture groups (MD 0.60 kg, 95% CI −0.20 to 1.39, p=0.14). Begg's test and funnel plots showed that the potential publication bias of the included studies was very slight (p>0.05). Conclusion: Acupuncture for simple obesity appeared to be an effective treatment, but more studies on the safety of acupuncture used to treat simple obesity are required.